Influence of Oxalic Acid Concentrations on The Growth of Molybdenum Disulfide via Spin Coating Technique - Tan, A. L.; Ng, S. S.; Hassan, H. Abu (2017)
In this context, the molybdenum disulfide (MoS2) films were grown by spin coating technique and thermal vapour sulfurization (TVS) under the condition of different oxalic acid concentrations. Atomic force microscopy (AFM) surface topography shows the improved homogeneity and higher compactness of films with the increasing acid concentration. However, high concentration favoured the formation of larger grains and poor continuity of films. These observations were further proven by the particle size distribution profile. Apart from that, two distinct Raman phonon modes of the MoS2 can be detected in all the deposited films. In addition, molybdenum dioxide (MoO2) was detected at higher acid concentration due to the slower rate of diffusion of sulfur atoms during the surface sulfurization. From the direct analysis of frequency difference between in-plane (E2g 1) and out-of-plane (A1g) phonon modes, it proves that multilayers of MoS2 films were synthesized. Ultraviolet-visible (UV-Vis) specular reflectance results also reveal that crystallite MoS2 films with the absorption peaks of 612 nm and 660 nm were detected.